Ноніусна адаптивна високоточна система стабілізації стохастичних технологічних процесів - Galay, V. М.; Silvestrov, A. M.; Shefer, O. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
Тhe operational use of methods of vernier identification and adaptation of the structure and parameters of an automatic control system with a standard model on an example ASCTP of an extract of quartzy handsets is considered.